2007
DOI: 10.1111/j.1346-8138.2006.00225.x
|View full text |Cite
|
Sign up to set email alerts
|

Expression patterns of proliferating cell nuclear antigen in trichloroacetic acid peeled skin

Abstract: This study was designed to investigate whether trichloroacetic acid (TCA) peeling induces cellular proliferation in human skin using an immunohistochemical method. A 40% TCA peel resulted in a greater number of proliferating cell nuclear antigen (PCNA)-immunopositive cells in the whole epidermis as compared with 60% TCA or phenol peels. This finding suggests that long-term and frequent TCA peelings of low concentration would require special attention for unexpected cutaneous lesions such as skin tumors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2008
2008
2012
2012

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 5 publications
1
9
0
Order By: Relevance
“…56 In our cases, there were 7 instances of PD (15.2%; 3 AK and 4 BD), and only two recurred (4.3%; one AK and one BD) during the 1-year follow-up period. If we consider the current results and previous reports, 57 phenol peels would not cause tumorigenesis in CR cases.…”
Section: Discussionsupporting
confidence: 57%
“…56 In our cases, there were 7 instances of PD (15.2%; 3 AK and 4 BD), and only two recurred (4.3%; one AK and one BD) during the 1-year follow-up period. If we consider the current results and previous reports, 57 phenol peels would not cause tumorigenesis in CR cases.…”
Section: Discussionsupporting
confidence: 57%
“…early and severe periodontitis, and/or esophageal, gastrointestinal and genital involvement [1,2]. KS results from recessive loss-of-function mutations of the KIND1 gene (now called FERMT1) that encodes the protein kindlin-1, a component of focal adhesions in epithelial cells [3]. KS results from recessive loss-of-function mutations of the KIND1 gene (now called FERMT1) that encodes the protein kindlin-1, a component of focal adhesions in epithelial cells [3].…”
Section: Letter To the Editormentioning
confidence: 99%
“…Jessner's solution represents a combination of resorcinol, salicylic and lactic acids in a sufficient quantity of ethanol [1]. The application of chemical peelings and microdermabrasion is associated with morphological changes reminiscent of wound healing activities in the skin [3]. Microdermabrasion involves the physical abrading of the skin with a high-pressure flow of crystals [2].…”
mentioning
confidence: 99%
“…Relative densities of positive reaction for those proteins were higher in the experimental group than in the control group. Researchers have suggested that rhGM-CSF induces other growth factors or cytokines in a paracrine manner and that these factors stimulate keratinocytes and fibroblasts (Yamamoto et al 2007;Haroon et al 1999).…”
Section: Discussionmentioning
confidence: 99%